Standard and increased canakinumab dosing to quiet macrophage activation syndrome in children with systemic juvenile idiopathic arthritis - Kostik, Mikhail M.; Isupova, Eugenia A.; Belozerov, Konstantin; Likhacheva, Tatyana S.; Suspitsin, Evgeny N.; Raupov, Rinat; Masalova, Vera V.; Chikova, Irina A.; Dubko, Margarita F.; Kalashnikova, Olga V.; Chasnyk, Vyacheslav G.; Cron, Randy Q. (Frontiers in Pediatrics, 2022)
Objective. Macrophage activation syndrome (MAS) is a life-threatening, potentially fatal condition associated with systemic juvenile idiopathic arthritis (sJIA). Interleukin-1 (IL-1) is a key cytokine in the pathogenesis of sJIA MAS. Many cases of MAS are medically refractory to traditional doses of biologic cytokine inhibitors and may require increased dosing. When MAS occurs in the setting of sJIA treated with the IL-1 receptor antagonist (IL-1Ra), anakinra, increased anakinra dosing may be beneficial. Increased dosing of another IL-1 inhibitor, canakinumab, a monoclonal antibody to IL-1β, has not been reported to treat refractory MAS in the setting of sJIA. Methods. Retrospective data collection extracted from the electronic medical record focused on canakinumab usage and dosing in 8 children with sJIA who developed MAS at a single academic center from 2011 to 2020. Results. Eight sJIA children (five girls) with median age 8.5 years (range, 0.9 to 14.2 years) were included in the present study. Five children developed MAS at disease onset and 3 during ongoing canakinumab therapy. MAS resolved in all 8 children with canakinumab treatment. When the canakinumab dosing was insufficient or MAS developed during canakinumab therapy, the dosing was temporally up-titrated (4 patients, maximum 300 mg per dose) without observed side effects. Conclusion. This report provides evidence for the efficacy and safety of short-term increased doses (2-3-times normal) of canakinumab in treating sJIA associated MAS. Further study of the efficacy and safety of increased doses of canakinumab for treatment of MAS in children with sJIA is warranted.